Law Enforcement Against Surveillance Of Illegal Gold Mining Crimes In Review Of Positive Law And Islamic Law (Case Study In Wasirawi Village, Masni District,Manokwari Regency, West Papua Province) - La Ode Musrifin (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2024)
The mining management system in Indonesia is pluralistic due to the various mining contracts or licenses currently in force. For this reason, it is necessary to take action in all components of the nation, including law enforcement, both in positive law and Islamic law. This research aims to find law enforcement against the supervision of illegal gold mining crimes by reviewing the perspective of positive law and Islamic law (case study in Wasirawi Village, Masni District, Manokwari Regency, West Papua Province). The method used in this research is a qualitative descriptive approach. The results of this study are as follows: First, the role of the government in curbing illegal nickel mining in Waserawi Village, Masni District, Manokwari Regency, West Papua Province, from all functions, still needs to be stronger. The mining sector is very vulnerable to violations of the law. Therefore, regulations are formed that can regulate the mining business sector, namely in Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining. Second, MUI, as an institution that provides fatwas, issued a fatwa on the law of environmentally friendly mining on 26 May 2011. The fatwa states that mining activities that do not bring prosperity to the community are haram. In Islamic law, illegal miners are included in the realm of ta‟zir punishment, so Ulil Amri can make Ijtihad to determine the type of punishment.